(untitled) (Journal of Information and Communication Technology, 2007)
This paper describes the design and implementation of prototype system, F200 for the enhanced dataflow diagram, called data flow net (DF net) (Tan, Yang, & Bian), 2006). The prototype system transforms the software systems designed in DF net to 00 design and implementation systemically, precisely and automatically. This has greatly enhanced the 00 methodology by synthesizing functional decomposition, which is a well-developed concept in traditional structured methodology. The prototype system facilitates the software designer to construct the functional analysis models for some of the use-cases in their own systems in DF net. Thereafter, together with remaining use-cases using any existing 00 software development methods, the whole systems can be implemented following current 00 design and implementation. This is very useful in realizing use-cases, especially those with more complex functions.